Study of Functional Outcome of Calcaneal Fractures with Percutaneous Cancellous Screws Fixation in Central Rural India - Vasant Gawande1 , Ashwin Chauhan2 , Kunal K. Saoji3 , Ankit Mittal4 , Suvarn Gupta5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Calcaneum fractures are nearly 2% of all adult fractures. Calcaneum is the main weightbearing bone in the foot. Mostly these fractures are caused by high energy trauma/fall from height leadingto various patterns of fractures. There are various method of treating such fractures but due to high rateof complications by open reduction and internal fixation hence middle path regime shall be discoveredfor treating most important weight bearing bone. Inevitable malunion and arthritis due to conservativemanagement can be avoided by percutaneous fixation.Material and Method: A prospective retrospective review of 12 patients with 16 calcaneal fractures whohad percutaneous reduction and screw fixation between January 2019 to April 2020 was done at at ShalinitaiMeghe Hospital and Research center Nagpur. These cases were managed with 3-4 percutaneous cancellousscrews.Results: The results were assessed with Calcaneal fracture scoring system and Maryland foot scoring systemand showed good to excellent functional results of complex intra-articular calcaneal fractures.Conclusion: Percutaneous method of fixation with Cancellous screws is a far superior modality of treatmentof calcaneal fractures in order to get better functional outcome with minimal complications.